The Perception of English Learning at SMAN 1 Sidrap on Students’ English-Speaking Confidence - Kartini; Buhari; Nurhikmah; Syahrir L; Sam Hermansyah (INTERACTION: Jurnal Pendidikan Bahasa, 2026)
This study explored students’ perceptions of English learning at SMAN 1 Sidrap and examined how those perceptions shaped their English-speaking confidence. A qualitative descriptive design was employed. Thirteen eleventh-grade students were selected through purposive sampling because they had participated in varied classroom speaking activities and represented different confidence levels. Data were collected through semi-structured interviews and classroom observation, supported by a speaking-confidence scale, and were analyzed using the interactive model of Miles, Huberman, and Saldaña: data collection, data condensation, data display, and conclusion drawing. Trustworthiness was established through credibility, transferability, dependability, and confirmability. The findings showed that most students perceived English as useful for further study, employment, and international communication. Discussions, presentations, role plays, speeches, drama, and group work were viewed as meaningful opportunities to practice English and strengthen confidence. Positive feedback from teachers, peer encouragement, and a non-threatening classroom atmosphere increased students’ willingness to communicate and classroom participation. Nevertheless, anxiety, fear of mistakes, limited vocabulary, and pronunciation difficulties still reduced confidence among some students. The study concludes that positive perceptions of English learning support higher speaking confidence by increasing motivation, lowering the affective filter, and strengthening students’ beliefs in their own ability. Teachers should therefore design interactive, supportive, and progressively challenging speaking activities.